Novel rare frameshift variation in aggressive periodontitis: Exomic and familial-screening analysis - Taiete, Tiago; Casati, Marcio Z.; Martins, Luciane; Andia, Denise C.; Mofatto, Luciana S.; Coletta, Ricardo D.; Monteiro, Mabelle F.; Araújo, Cássia F [UNESP]; Santamaria, Mauro P. [UNESP]; Corrêa, Mônica G; Sallum, Enilson A.; Nociti, Francisco H.; et al. (Wiley, 2020)
BACKGROUND: Aggressive periodontitis (AgP), currently periodontitis grade C, presents early onset, rapid progression, and a poorly established genetic association. Thus, this study aimed to identify genetic variants associated with AgP via whole exome sequencing (WES) through a familial screening approach. METHODS: WES was performed in two nuclear families, including a proband and a parent affected by AgP and an unaffected parent and sibling. Common variants among affected individuals, excluding those common to healthy people, from each family, composed the data set associated with AgP. In silico analysis evaluated the impact of each variant on protein structure and protein-protein interactions. Moreover, identified deleterious variants were validated in a populational analysis (n = 96). RESULTS: The missense single nucleotide variations (SNVs) rs142548867 in EEFSEC (c.668C>T), rs574301770 in ZNF136 (c.466C>G), and rs72821893 in KRT25 (c.800G>A) and the frameshift indels rs37146475 in GPRC6A (c.2323-2324insT) and c.1366_1372insGGAGCAG in ELN were identified in AgP and have a predicted functional impact on proteins. In silico analysis indicated that the indel in GPRC6A generates a loss of the C-terminal tail of the Gprca protein. Furthermore, this SNV was significantly associated with AgP in a population-based investigation. CONCLUSION: Novel frameshift variation in GPRC6A (c.2323-2324insT) was identified as a potential genetic alteration associated with AgP occurrence.
Keywords: genetic association studies; genetic markers; genetic variation; genotype; periodontal diseases